Processing of Tofu industrial wastewater by electrocoagulation method using aluminum (Al) electrode at various electrical current and contact time - Rachmat, Addy; Fatma, Fatma; Pratama, Nisa Manora; Musifa, Eva (Indonesian Journal of Chemical Science, 2025)
This research aims to determine the effect of varying voltage and contact time on reducing levels on Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), Total Dissolved Solids (TDS) and ammonia as well as increasing pH values ​​in tofu industrial wastewater by electrocoagulation using Aluminum electrodes. There were 4 variations of voltage (10,20,30,4 0A) and 5 variations of contact time (30,60,90,120,150 minutes). Analysis of COD levels and ammonia levels was carried out using a UV-Vis spectrophotometer, analysis of TSS levels gravimetrically using Whatman filter paper No. 42, analysis of TDS levels with gravimetrically, and analysis of pH values ​​by a pH meter. The best results were obtained from treatment at voltage of 40 A and a contact time of 150 minutes with the highest efficiency of reducing COD, TSS, TDS, ammonia levels respectively at 90.35; 92; 66; 85% and the highest increase in pH value was 108%. The results of the diversity analysis or Tukey's advanced test showed that at the 5% level each treatment had a significant effect on reducing COD, TSS, TDS and ammonia levels as well as increasing the pH value. Chemical kinetics analysis of the reduction in COD and TSS levels showed results that were close to first orde linear and obtained R2 and k values ​​respectively of (0.9904; 0.0164); (0.9952; 0.0182) at voltage variation of 40 A